Defect-rich MoSx/carbon nanofiber arrays on carbon cloth for highly efficient electrocatalytic hydrogen evolution. (27th December 2018) - Guo, Xiaosong; Wang, Liu; Zeng, Jing; Shao, Yalong; Cui, Wenyu; Zhang, Chi; Wang, Wenjing; Hao, Chuncheng; Li, Guicun
Abstract: Engineering MoS2 catalysts with more active sites and higher conductivity is an effective way to improve its electrochemical activity. Herein, defect-rich amorphous MoS x /carbon nanofiber (CF) arrays on carbon cloth (CC) support (denoted as MoS x /CF/CC) was designed and fabricated, which served as an efficient free-standing electrocatalyst for hydrogen evolution reaction (HER) in acid media. This architecture was beneficial to expose more active catalytic sites and improve the electron/ion transport. In addition, abundant defects altered preferred growth direction of MoS x, resulting in the formation of irregular MoS x particles at the surface of CF arrays. The as-synthesized MoS x /CF/CC-2 exhibited excellent stability and superior HER activity, with a small onset overpotential (107 mV) and low Tafel slope (51 mV dec −1 ). Such excellent electrochemical performance was attributed to the enriched active sites and shortened charge diffusion distance. This work would pave a new way for rational design and fabrication of defect-rich MoS x -based composite electrode for renewable energy applications. Highlights: Defect-rich MoS x /carbon nanofiber arrays on carbon cloth support were fabricated. Abundant defects altered preferred growth pattern of MoS x . Defect-rich MoS x could provide more active sites to promote the HER performance. Carbon nanofiber/carbon cloth was a supporting material for defect-rich MoS x .